Riscritture del romance nel secondo Novecento italiano - Stefano Nicosia (Between, 2013)
Many authors in the last century offer us the possibility to look at romance through their rewriting of Italian tradition, but they also offer the possibility to look at rewriting through romance. A systematic examination of every single work would need an article itself. Here the focus is rather on the phenomenon and its implications with tradition and its transformations; and on the intellectual context where they take place. Despite the very core of the poetics of rewriting can be located between the Sixties and the Eighties, these palimpsests go further, into the Nineties. From Calvino, Manganelli and Sanguineti, to Celati, Bufalino and Santagata, we are able to look at different declensions of rewriting. Through these texts and the techniques they are built with, it is possible to verify the strength and the qualities of some cultural and intellectual practices, which can be related to a coherent Italian postmodern poetics, which operates through the reuse of traditional materials. These reuse should be seen – and this is one of the cues and conclusions the article would like to offer – as a vital way of reproducing stories and genres in the postmodern era.